Avaliação do comportamento mecânico e tribológico através de ensaios de esclerometria retilínea de superligas de cobalto - Bragatto Junior, Luiz Carlos (2016)
Cobalt base superalloys are used in many industrial applications due to its characteristic of maintaining its mechanical properties at high temperatures. Three different cobalt superalloys were produced by cast process with chemical compositions close to those of commercial alloys Stellite 6, Triballoy T-400, and an alloy Co-Cr-Fe. To better understand the mechanical and tribological behavior of these superalloys, scratch tests were performed using a rockwell C indenter with two different configurations: a single pass with different normal loads, 5 to 20N, and the scratch speed, 0.01 mm / s to 1 mm / s; and one with several passes, 1 to 15 passes, maintaining a constant scratching speed of 0.1 mm / s and loads, from 5 to 100N. In these tests were analyzed the scratch hardness of each material, the fab factor, which evaluates the ratio of the area of the material displaced to the side and the area of scratch groove, the degree of penetration, which is a ratio between the depth and the width of the scratch, and additionally were evaluated the wear rates. The abraded surface was analyzed by 3D profilometry and scanning electron microscope image to evaluate the dominant wear mechanism and the wear rate of each material. In all the three alloys the predominant micromechanisms was microploghing. In the Co-Cr-Fe alloy, the predominant mechanism was ductile at all settings of the tests. Already in tests with Stellite 6 and Triballoy T-400 alloys, cobalt matrix showed ductile behavior and hard phases, carbides and laves phase showed brittle behavior, and were fractured. In the alloys Stellite 6 and Triballoy T-400, tests with several passes was observed plastic deformation of the matrix of cobalt which covered the carbides and laves phases, respectively, and also a mechanical mixing due to excessive fracture of carbides and laves phases that are mixed with cobalt matrix. The alloy Co-Cr-Fe showed a lower performance for resistance to wear, and Stellite 6 and Triballoy T-400 alloys showed similar behavior and better wear resistance.